Case Report: Whole Exome Sequencing Identifies Compound Heterozygous Variants in TSFM Gene Causing Juvenile Hypertrophic Cardiomyopathy - Yang, Jamie O.; Shaybekyan, Hapet; Zhao, Yan; Kang, Xuedong; Fishbein, Gregory A.; Khanlou, Negar; Alejos, Juan C.; Halnon, Nancy; Satou, Gary; Biniwale, Reshma; Lee, Hane; Van Arsdell, Glen; et al. (Frontiers in Cardiovascular Medicine, 2022)
We report a case of hypertrophic cardiomyopathy and lactic acidosis in a 3-year-old female. Cardiac and skeletal muscles biopsies exhibited mitochondrial hyperplasia with decreased complex IV activity. Whole exome sequencing identified compound heterozygous variants, p.Arg333Trp and p.Val119Leu, in TSFM, a nuclear gene that encodes a mitochondrial translation elongation factor, resulting in impaired oxidative phosphorylation and juvenile hypertrophic cardiomyopathy.